LA SEGURIDIZACIÓN DE LA CONFERENCIA REGIONAL SOBRE MIGRACIÓN - Solís Vargas, María Eugenia (2018)
This article analyzes how the prioritization of safety approaches together with changes in the security complex, have influenced the discourse of the Regional Conference on Migration in the I and XIX conference. Using content analysis to mark the discursive differences in the Regional Conference on Migration, between 1996 and 2014. Demonstrating that the conference has gone through a process of change, passing from a human rights approach to one of security.